Viktimisasi Struktural terhadap Pekerja Twin Plaza Hotel terkait Standar Upah Minimum Sektoral Provinsi DKI Jakarta - Figal Fathrusi Kusbiantoro; Lucky Nurhadiyanto (Universitas Budi Luhur, 2019)
This study discusses how victimization workers in the Twin Plaza Hotel can happen using victimology theory and structural victimization. The application of structural victimization theory, is expected to know how workers or employees can be victims, as well as how the hotel Twin Plaza companies that are the owners of capital commit violations and non-violent crimes against His workers use the theories of victimology and structural victimization. This study uses a qualitative research approach and described using descriptive type, data collection done by interview, as well as conducting studies on the literature or related documents. The results of this study have seen and described the process of occurrence of victimization in the hotel Twin Plaza, impact as well as how to overcome violations and non-violent crimes committed by the company against its workers.